Avaliação dos efeitos da técnica da dupla camada na soldagem do aço ASTM A 516 grau 60 - Cruz, Ricardo Liarth da Silva (2006)
Steel ASTM A 516 Grade 60 is connected to a manganese structural steel, widely used in oil industry operations in storage, transport and processing of petroleum products in conditions that present requirements of toughness. When the repair of structures constructed with the conventional steel involves welding, there is the formation of martensitic structure in the heat affected zone (HAZ) and the establishment of residual stresses along the joint. The repair procedures for ASTM A516 Grade 60 establish the use of a heat treatment for stress relieving after welding, such as an alternative treatment is able to reduce / minimize the harmful effects arising in the region of the weld. However, they can sometimes be technically impractical or represent a significant cost increase, so that a welding procedure without post weld heat treatment (TTPs), which results in low levels of residual stresses and adequate chemical and mechanical properties of the joint is extremely important. In this context, this work has been proposed to contribute to studies of repair by welding, quality and without the need for TTPs, by applying the technique of the double layer. The essays in this work were conducted on samples of steel ASTM A 516 Grade 60 to 38 mm thick, welded manually with basic electrodes, beveled joints in K and semi V, which were evaluated in the condition as received; soldier with the conventional procedure without TTPs and TTPs, and soldiers with the technique of the double layer. The energy relations for the application of the double layer were defined after the application of conventional test Higuchi (hardness) and modified (microstructure). For all joints were evaluated the profiles of microhardness, microstructure, the energy absorbed the impact and stress profiles residuais.Os results demonstrated that the application of welding technique with double-layer, using appropriate combinations of welding power, defined Test Higuchi, can achieve reductions in levels of hardness in HAZ; microstructural refinement, improved final mechanical properties, but with signs of high residual stresses in the weld metal and base metal.